Study Of Perception Public At System Pawnshop Syariah Branch Tanjung Market In Jember Yani Dahliani1, Yuniorita Indah Handayani 2,Helmi Agus Salim 3, etc Author Affiliation1, Author Affiliation2, Author Affiliation3, etc Email: yani@itsm.ac.id, yuniorit - Dahliani, Yani; Indah Handayani, Yuniorita; Agus Salim, Helmi (Institut Teknologi dan Sains Mandala, 2024)
The financial instution is delived into, namely bank financial instutions and non-bank financial instutions. One of the non-bank financial instutions is instution in the form of public company (perum). The background of this research is to know the views and perceptions of the society to the pawnshops of sharia branch tanjubg marketin Jember as well as the factors that determine the community to choose pawnshops as one source to abtain funds. The problem in this research is how is the society perception of sharia pawn system in pasar tanjung and to know what are the factors that determine the people prefer anh how sharia pawnshops in running the system and whether people understand about how the system implemented by pawnshop sharia.The purpose of this descriptive research of sharia pawn system. The results of research that has been done shows that the community is very supportive of sharia pawnshops, with sharia pawnshops can help the community down in obtaining funds quickly easil, greatly assist the community in its financial problems to meet their needs but the lack of socialization conducted by pawnshops sharia making people who pawned gold or other goods made ignorance and lack of understanding of the system and akad used by sharia pawnshops, this resulted in 100% of respondents experiencing a lack of understanding of the system, products and contracts implemented by the sharia pawnshops.